KAJIAN UNSUR BUDAYA JAWA DAN NILAI SOSIAL NOVEL GADIS PANTAI KARYA PRAMOEDYA ANANTA TOER SEBAGAI MATERI PEMBELAJARAN SASTRA DI SMA - Puspitasari, Ratna Nisrina; Suyitno, Suyitno; Mulyono, Slamet (Universitas Sebelas Maret, 2020)
The research aims to describe (1) the author’s background of the Gadis Pantai nove , (2) disclosure of elements of Javanese culture; (3) social values in the Gadis Pantai novel; and (4) the relevance of Gadis Pantai novel as literature learning material in senior high school. This research uses qualitative descriptive method. The data source used is in the form of documents and informants. The sampling technique uses purposive sampling. Data collection techniques use document analysis and interview techniques. The validity of the data is done by theoretical triangulation and source triangulation. Data analysis using interactive analysis. The results of the study show: (1) the author’s background of the Gadis Pantai novel that is closely related to family and social backgrounds, (2) the disclosure of elements of Javanese culture, including the use of the language of the Javanese community according to position, age, status, and level of familiarity, the Javanese knowledge system that is culturally based on the Dutch colonial knowledge system, the Javanese social system adheres to a strong feudal system. the system of technology and equipment that develops in the life of the Javanese people has developed, the livelihoods of the Javanese people are influenced by geographical conditions and the surrounding environment, the belief system and religion of the Javanese community are influenced by animist culture and dynamism, the diversity of arts developed in Javanese societ,; (3) social values which include the value of perseverance / hard work, honesty values, values of helpful help, politeness values, individual values, (4) Gadis Pantai novel can be used as literary learning material in senior high schools for class X, XI, and XII, especially in learning in KD 3.7 and 4.7 in special class XI and KD 3.8 and KD 4.8 in class XII required.